TG13 diagnostic criteria and severity grading of acute cholecystitis (with videos). Issue 1 (January 2013) - Yokoe, Masamichi; Takada, Tadahiro; Strasberg, Steven M.; Solomkin, Joseph S.; Mayumi, Toshihiko; Gomi, Harumi; Pitt, Henry A.; Garden, O. James; Kiriyama, Seiki; Hata, Jiro; Gabata, Toshifumi; Yoshida, Masahiro; et al.
Abstract Since its publication in 2007, the Tokyo Guidelines for the management of acute cholangitis and cholecystitis (TG07) have been widely adopted. The validation of TG07 conducted in terms of clinical practice has shown that the diagnostic criteria for acute cholecystitis are highly reliable but that the definition of definite diagnosis is ambiguous. Discussion by the Tokyo Guidelines Revision Committee concluded that acute cholecystitis should be suspected when Murphy's sign, local inflammatory findings in the gallbladder such as right upper quadrant abdominal pain and tenderness, and fever and systemic inflammatory reaction findings detected by blood tests are present but that definite diagnosis of acute cholecystitis can be made only on the basis of the imaging of ultrasonography, computed tomography or scintigraphy (HIDA scan). These proposed diagnostic criteria provided better specificity and accuracy rates than the TG07 diagnostic criteria. As for the severity assessment criteria in TG07, there is evidence that TG07 resulted in clarification of the concept of severe acute cholecystitis. Furthermore, there is evidence that severity assessment in TG07 has led to a reduction in the mean duration of hospital stay. As for the factors used to establish a moderate grade of acute cholecystitis, such as leukocytosis, ALP, old age, diabetes, being male, and delay in admission, no new strong evidence has been detected indicating that a change in the criteria used in TG07 is needed. Therefore, it was judged that the severity assessment criteria of TG07 could be applied in the updated Tokyo Guidelines (TG13) with minor changes. TG13 presents new standards for the diagnosis, severity grading and management of acute cholecystitis.